Partnering for UN SDG #17: a social marketing partnership model to scale up and accelerate change. Issue 1 (29th September 2021) - Duane, Sinead; Duane, Sinead; Domegan, Christine; Bunting, Brendan
Abstract : Purpose: The United Nations (UN) 17 Sustainable Development Goals (SDG) places partnerships as a vital mechanism, which strengthens the implementation of change strategies. The SDG targets are ambitious; acknowledging the interconnected multifaceted issues that are currently facing society. Similarly, social marketing thought is transitioning to embrace systemic change strategies, realising no one organisation can have an impact on the emerging grand challenges. Partnerships are the 5th P in the social marketing mix, however, partnerships is also a nebulous term which has been criticised for lacking theoretical development. This study aims to answer the call from both the UN and social marketing community for further research to guide the development and implementation of impactful transformative partnerships. Design/methodology/approach: A robust mixed method approach to develop and test a social marketing partnership model is presented. Trust and relationship commitment are at the forefront of successful partnership exchanges. Morgan and Hunt's (1994) trust and relationship commitment model is extended into the social marketing domain. Findings: The findings validate Hasting's (2003) call for social marketers to listen to their commercial marketing counterparts, positioning trust and commitment as essential to change strategies. As the degree of complexities in the multifaceted world continues to accelerate, partnerships for change (UN SDG #17) will pay off, driving more effective and smarter collaborations amongst a diverse range of stakeholders at different levels in different networks. Partnerships will elevate social marketing to deliver systemic transformation for complex problems with far reaching collective and sustainable consequences. Research limitations/implications: With trust/mistrust critical to successful exchanges and exchange central to social marketing, quantitative measurement of the antecedents to and outcomes of partnerships can inform the evaluation, impact and management of social marketing interventions. Practical implications: Three contributions are made, which support the selection, implementation and evaluation of social marketing partnerships. Key social marketing partnership characteristics are operationalised supporting the partnership selection process. Measurement scales are developed to assist in evaluating partnership relationships over time. The model is empirically tested to investigate the relationships between key mediating variables of social marketing partnerships. Originality/value: This paper presents a validated 5th P Partnership model for social marketers, accelerating social marketing's capacities to deliver systemic transformation for complex problems with far reaching collective and sustainable consequences and UN SDG #17.